GROWTH AND SECONDARY METABOLITES OF BASIL, MINT AND THYME AS AFFECTED BY LIGHT - SHAHRAM SHARAFZADEH, (International Journal of Pharma and Bio Sciences, 2012)
Basil (Ocimum basilicum L.), mint (Mentha sp.) and thyme (Thymus vulgaris L.) are the members of the family Lamiaceae. The Lamiaceae plant family is one of the largest families among the dicotyledons, many species being highly aromatic, due to the presence of various terpenoids and phenolic compounds. Growth, Chemical profile and accumulation level of a special metabolite in plant tissues can be influenced by several environmental factors such as light quality, light intensity and photoperiod. Determination of optimum light conditions for chemical accumulation as well as plant growth and development is an important topic in obtaining the increased concentration of phytochemicals. This review focuses on the experimental researches regarding the effects of light conditions on growth and secondary metabolites of basil, mint and thyme.